Carotid Cavernous Fistulae: Indications for Urgent Treatment - Halbach, Van V.; Hieshima, Grant B.; Higashida, Randall T.; Reicher, Murray (American Journal of Neuroradiology, 1987)
Angiographic and clinical data from 155 patients with carotid cavernous fistulae were retrospectively reviewed to determine angiographic features associated with increased risk of morbidity and mortality. These features included presence of a pseudoaneurysm, large varix of the cavernous sinus, venous drainage to cortical veins, and thrombosis of venous outflow pathways distant from the fistula. Clinical signs and symptoms that characterized a hazardous carotid cavernous fistula included increased intracranial pressure, rapidly progressive proptosis, diminished visual acuity, hemorrhage, and transient ischemic attacks. Cortical venous drainage from the carotid cavernous fistula is secondary to occlusion or absence of the normal venous outflow pathways and is associated with signs and symptoms of increased intracranial pressure and an increased risk of intraparenchymal hemorrhage. Angiographic demonstration of a cavernous sinus varix, with extension of the sinus into the subarachnoid space, is associated with an increased risk of fatal subarachnoid hemorrhage. Identification of these high-risk features provides a basis for making decisions about treatment.